2022
DOI: 10.1002/smll.202203412
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Cation Pillar Effects Achieving High Capacity in Li‐Rich Layered Oxide, Li2MnO3‐LiMeO2 (Me = Ni, Co, Mn)

Abstract: Intensive research is underway to further enhance the performance of lithium‐ion batteries (LIBs). To increase the capacity of positive electrode materials, Li‐rich layered oxides (LLO) are attracting attention but have not yet been put to practical use. The structural mechanisms through which LLO materials exhibit higher capacity than conventional materials remain unclear because their disordered phases make it difficult to obtain structural information by conventional analysis. The X‐ray total scattering ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Actually, the lattice collapse is caused by the oxidation of lattice O 2– ions at a high charging voltage due to the covalency between TM and oxygen ions. The O 2p band formed holes that released the anion–anion electrostatic repulsion between the neighboring oxygen layers, leading to the shrinkage of the c-lattice in the deep delithiation state. By combining Rietveld refinements of in situ XRD, the variations of the c-lattice and the volume parameter are obtained, as shown in Figure c,d. With the continuous removal of Li + , the c value first increases and then decreases, which is in good accordance with the variation of the interlayer spacing between the two adjacent oxygen slabs mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the lattice collapse is caused by the oxidation of lattice O 2– ions at a high charging voltage due to the covalency between TM and oxygen ions. The O 2p band formed holes that released the anion–anion electrostatic repulsion between the neighboring oxygen layers, leading to the shrinkage of the c-lattice in the deep delithiation state. By combining Rietveld refinements of in situ XRD, the variations of the c-lattice and the volume parameter are obtained, as shown in Figure c,d. With the continuous removal of Li + , the c value first increases and then decreases, which is in good accordance with the variation of the interlayer spacing between the two adjacent oxygen slabs mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, the occupancies of Me were refined by assuming that only Ni migrated to the tetrahedral site and octahedral sites in the Li layer. 23 The equivalent analyses using Mn as the migrating cation validated this approach. Using Ni or Mn as the migrating cations gave almost identical results (Table S4).…”
Section: Pdf Analysesmentioning
confidence: 86%
“…[83] Hiroi et al concentrated on the role of native 3d metals in Li-rich NCM as pillars. [153] The X-ray total scattering showed that TMs moved to octahedral and tetrahedral sites in the Li layer upon charge. The TMs in the octahedral sites acted as rigid pillars, while the TMs in the tetrahedral sites acted as adaptive pillars moving back to the TM layer upon lithiation (Figure 11b).…”
Section: Inhibition Of Cation Migrationmentioning
confidence: 99%
“…Adapted under the terms of the CC‐BY Creative Commons Attribution 4.0 International license (https://creativecommons.org/licenses/by/4.0). [ 153 ] Copyright 2022, The Authors, published by Wiley‐VCH. c) Change of layer stacking order from the O3 to the O2 phase triggers reversible out‐of‐plane TM migration.…”
Section: Strategies For Reversible Oxygen Redoxmentioning
confidence: 99%
See 1 more Smart Citation